Implementasi pemasaran digital guna optimalisasi pemasaran, studi kasus pada “Ganezza Bakery” - Indah Kumala Putri; Candraningrat Candraningrat (Universitas Pendidikan Indonesia (UPI), 2023)
Ganezza Bakery is a commercial Micro, Small and Medium Enterprises (MSME) established in 2017 and located on Jl. Tambak Asri No. 4. Ganezza Bakery sells and accepts orders for various breads and cakes. Based on the results of observations and interviews, Ganezza Bakery MSME have not implemented digital marketing in their marketing, so their marketing is still carried out traditionally. MSME are known to the public through customers who have bought their products and the surrounding community. As a result, small-scale marketing is less than optimal. Where in reality, currently business people, especially MSME, must be able to stay updated by keeping abreast of developments in information technology by implementing online sales or through social media or online shopping. Through online marketing can help increase public knowledge about Ganezza Bakery MSME. Prospective consumers can find information more easily without having to travel long distances to reach the MSME Ganezza Bakery store. Marketing activities on the Internet are also more efficient and effective than direct marketing, such as opening stores or participating in trade shows at home and abroad. In addition, online marketing steps do not require a lot of time, energy, and material so it is easier to implement.